Evaluating the efficacy of a Mycobacterium bovis vaccine in feral swine - Topliff-Yee, Elizabeth Kathrine, author; Holt, Timothy, advisor; Nol, Pauline, committee member; Bowen, Richard, committee member (Colorado State University. Libraries, 2017)
Bovine tuberculosis (bTB) is a globally significant zoonotic disease caused primarily by Mycobacterium bovis (M. bovis) transmission between wildlife, domestic livestock, and humans. Unfortunately in wildlife reservoirs of bTB, disease rates are increasing worldwide due to ecological dynamics and challenges in wildlife management. Despite effective, long-standing M. bovis eradication programs in the US, expanding wildlife reservoir habitat and importation of people, animals, and products from the Mexican dairy industry have become sources of zoonotic bTB infection. Currently, no tuberculosis vaccine is labeled for use in animals, although a vaccine could provide a new tool in preventing bTB in wildlife and domestic livestock. Bacille Calmette-Guerin (BCG), a live, attenuated M. bovis strain vaccine used for tuberculosis prevention in humans has been variably effective in reducing bTB development in studies on various species. We hypothesize that Texas-origin feral swine vaccinated orally with either modified-live BCG or inactivated M. bovis vaccine will have fewer, less severe lesions than non-vaccinated feral swine after virulent M. bovis challenge. In this study we test this hypothesis along with the immunologic response to vaccination and infection by measuring antibody levels in vaccinated and unvaccinated swine. Our results demonstrate that vaccination with BCG or inactivated strains of M. bovis do not confer protection against infectious challenge with a virulent Michigan strain of M. bovis.
Keywords: bovine; swine; vaccine; tuberculosis; Mycobacterium; BCG